Modeling Wave Energy Dissipation by Bottom Friction on Rocky Shores - César Acevedo-Ramirez; Olavo B. Marques; Falk Feddersen; Jamie H. MacMahan; Sutara H. Suanda (Journal of Marine Science and Engineering, 2026)
Rocky shores are characterized by rough, multi-scale bathymetric variations that result in enhanced wave energy dissipation by bottom friction compared to sandy beaches. Realistic SWAN simulations of surface gravity waves across the rocky shores of Monterey (CA, USA) are conducted, and model results are compared to 20 inner-shelf observational sites spanning 34–5 m water depth. The wave field was highly variable during the study, including alternately low energy waves dominated by southern swell and higher energy local waves aligned with strong north-westerly winds. Including a modified bottom friction parameterization is required for the model to reproduce bulk wave statistics with high skill across the entire inner shelf. The SWAN simulation with the default bottom friction parameterization overestimates significant wave height relative to observations because the friction factor fe parameterization has a maximum value of 0.3. Additional simulations included two empirical formulations relating fe to the normalized wave excursion Ab/kN in the large roughness regime Ab/kN

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Citizen science reveals waterfowl responses to extreme winter weather - Nicholas M. Masto; Orin J. Robinson; Michael G. Brasher; Allison C. Keever; Abigail G. Blake‐Bradshaw; Cory J. Highway; Jamie C. Feddersen; Heath M. Hagy; Douglas C. Osborne; Daniel L. Combs; Bradley S. Cohen (Global Change Biology, 2022)
Global climate change is increasing the frequency and severity of extreme climatic events (ECEs) which may be especially detrimental during late‐winter when many species are surviving on scarce resources. However, monitoring animal populations relative to ECEs is logistically challenging. Crowd‐sourced datasets may provide opportunity to monitor species' responses to short‐term chance phenomena such as ECEs. We used 14 years of eBird—a global citizen science initiative—to examine distribution changes for seven wintering waterfowl species across North America in response to recent extreme winter polar vortex disruptions. To validate inferences from eBird, we compared eBird distribution changes against locational data from 362 GPS‐tagged Mallards ( Anas platyrhynchos ) in the Mississippi Flyway. Distributional shifts between eBird and GPS‐tagged Mallards were similar following an ECE in February 2021. In general, the ECE affected continental waterfowl population distributions; however, responses were variable across species and flyways. Waterfowl distributions tended to stay near wintering latitudes or moved north at lesser distances compared with non‐ECE years, suggesting preparedness for spring migration was a stronger “pull” than extreme weather was a “push” pressure. Surprisingly, larger‐bodied waterfowl with grubbing foraging strategies (i.e., geese) delayed their northward range shift during ECE years, whereas smaller‐bodied ducks were less affected. Lastly, wetland obligate species shifted southward during ECE years. Collectively, these results suggest specialized foraging strategies likely related to resource limitations, but not body size, necessitate movement from extreme late‐winter weather in waterfowl. Our results demonstrate eBird's potential to monitor population‐level effects of weather events, especially severe ECEs. eBird and other crowd‐sourced datasets can be valuable to identify species which are adaptable or vulnerable to ECEs and thus, begin to inform conservation policy and management to combat negative effects of global climate change.

Fifty-nine microsatellite markers for hybrid classification studies involving endemic Florida Mottled Duck (Anas fulvigula fulvigula) and invasive Mallards (A. platyrhynchos) - Seifu Seyoum; Michael D. Tringali; Ronald R. Bielefeld; Jamie C. Feddersen; Richard J. Benedict; Andrew T. Fanning; Brandon L. Barthel; Caitlin Curtis; Cecilia Puchulutegui; Alicia C. M. Roberts; Vicki L. Villanova; Emily C. Tucker (Conservation Genetics Resources, 2012)